‘Learning the rules of the game‘: Emotional labor and the gendered academic subject in the United States - Bartos, Ann E.; Ives, Sarah (Gender, Place & Culture, 2019)
In this article, we investigate how entrenched sexism in higher education can take root in graduate school, where many of us learn the ‘rules of the academic game’ through our roles as teaching assistants (TAs). Feminist and antiracist scholars have documented how these ‘rules of the game’ are scripted on different academic bodies. We focus this article on the stubborn persistence of sexism in university life through the everyday, mundane forms of emotional labor and care that TAs feel obligated to perform. As the current #MeToo movement reminds us, sexism, sexist exploitation, and oppression are as evident today as they were decades ago when feminist scholars and activists challenged the masculinism of geographical discourse through examinations of power, knowledge, and subjectivity. Our research returns to these themes by examining TAs’ experiences of sexism in the classroom through the lens of critical care ethics. A focus on TAs brings attention to the constitution of the gendered academic subject and identifies the emotional labor required to manage this subject. We believe that the durability of sexism warrants an investigation of the sites where women learn their ‘place’ in the academy.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; charge émotionnelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; stratégie féministe; systèmes d'oppressions; thématiques; travail; universitaires; éducation; états-unis

Sub Rosa - Dawn, Amber (XYZ éditeur, 2019)
Les filles sont bien traitées, rue Sub Rosa. Elles n’ont jamais faim, jamais froid, jamais mal. Elles sont entre de bonnes mains, des mains qui leur tendent tout ce dont elles ont besoin… à une condition. Il faut accepter de combler les désirs des hommes de la ville venus faire un tour dans ce lieu surnaturel, caché, où leurs fantasmes deviennent réalité – pourvu, bien sûr, qu’ils aient un peu d’argent sur eux. Petite a tout pour se tailler une place de choix parmi les Splendides de Sub Rosa. Mais parviendra-t-elle à oublier sa vie d’avant et à exploiter son don au service de sa nouvelle maison?
Keywords: adolescence; approches et analyses; arts; corps; discipline; inégalités; patriarcat; roman; sexisme; systèmes d'oppressions; thématiques; travail; travail du sexe-prostitution; violences; études littéraires

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible